Answer:
(3x+1)(x+3) is the factorised form for the expression.
Step-by-step explanation:
:3
x
2
+
10
x
+
3
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
is the factorised form for the expression.
A square rotated about its center by 360º maps onto itself at 4 different angles of rotation. You can reflect a square onto itself across 4 different lines of reflection.
Answer:
Step-by-step explanation:
a. 4x+4y
b. 8a+24b
c. 6x+33y
d. 63a+54b
e. 3ac+bc
f. 2xy+11yz
Answer:
787592800
Step-by-step explanation:
Hi there,
If you round this answer to the nearest tens place, it would be 787592800. Since the 799 is closer to 800 rather than 790, it would round up and change the last three digits of the number instead of the usual two digits.
Hope this answer helps. Cheers.
Answer:
![\boxed{\mathrm{view \: attachment}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cmathrm%7Bview%20%5C%3A%20attachment%7D%7D)
Step-by-step explanation:
The zeros of a function is where the function crosses the x-axis. The x-intercepts are the zeros of a function.
![f(x) = (x - 1)(x - 7)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20-%201%29%28x%20-%207%29)
Let output equal to 0.
![0 = (x - 1)(x - 7)](https://tex.z-dn.net/?f=0%20%3D%20%28x%20-%201%29%28x%20-%207%29)
Set factors equal to 0.
![x-1=0\\x=1](https://tex.z-dn.net/?f=x-1%3D0%5C%5Cx%3D1)
![x-7=0\\x=7](https://tex.z-dn.net/?f=x-7%3D0%5C%5Cx%3D7)
The zeros of the function are
and
.